Correlation of sociodemographic variables and interpersonal sources of stress at work among miners - Kulić, Ljiljana; Galjak, Milivoje; Jovanović, Jovana (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Some professions are somewhat more exposed to stress and have been the subject of research for a long time, and research of occupational stress among employees at workplaces with a special health risk is of a special significance. That is the case with miners. The aim of the study was an assessment of the relation between the sociodemographic variables and interpersonal sources of stress at work among miners. Methods. The study was designed as a cross-sectional study and covered 170 respondents, classified into two groups: a study group comprised of miners (n = 142) and a control group (n = 28) comprised of administrative workers. The research was conducted at the Occupational Medicine Service of the Health Center Zvečan and at the Institute of Occupational Medicine in Niš. The questionnaire on the basic sociodemographic indicators of respondents, the Intrapersonal and Interpersonal Related Stressors Questionnaire (IRS), the Work Ability Index Questionnaire (WAI), the General Health Questionnaire (GHQ), the Copenhagen Burnout Inventory (CBI) and the Questionnaire on the stressors were used in this research. Results. Statistically, the miners consumed alcohol significantly more than the respondents from the control group (68.30% vs. 25.00%; p
Keywords: miners; sociological factors; interpersonal relations; stress, psychological; risk factors; occupational exposure; surveys and questionaires